2011
DOI: 10.7182/prtr.21.2.2001j18x785u10hg
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and addressing barriers to African American and non—African American families' discussions about preemptive living related kidney transplantation

Abstract: Families identified several barriers to discussing preemptive LRKT that could be addressed by social workers. Further research must be done to determine whether social workers need to tailor interventions to address families' cultural differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
0
36
2
Order By: Relevance
“…As patients with ESRD commonly avoid accepting donor offers to protect donor wellbeing or asking others to donate, 13,19,21,[70][71][72] patients may find it helpful to refer their family members to Infórmate to raise awareness of LKD as a treatment option and inform them about the process of becoming a donor. UCD participants had higher posttest knowledge gains than did NMH participants, most likely because website content was closely aligned to NMH's HKTP curriculum.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As patients with ESRD commonly avoid accepting donor offers to protect donor wellbeing or asking others to donate, 13,19,21,[70][71][72] patients may find it helpful to refer their family members to Infórmate to raise awareness of LKD as a treatment option and inform them about the process of becoming a donor. UCD participants had higher posttest knowledge gains than did NMH participants, most likely because website content was closely aligned to NMH's HKTP curriculum.…”
Section: Discussionmentioning
confidence: 98%
“…8 Sociocultural barriers to living kidney donation (LKD) specifically identified in Hispanics include: donor and recipient misconceptions about LKD, 13,14 fears about not being able to have children, 13 life expectancy concerns, 14 language barriers, 13,15 family discouragement, 13 and immigrant status issues. 16 Hispanics' concerns about LDKT shared with other minority populations include: lack of knowledge about LKD, 8,13,[17][18][19][20] fear of surgery, 14,17,19 financial concerns, 13,19,21,22 and distrust of the medical establishment. 16,17,19 Culturally competent 23 interventions have been increasingly used to reduce health disparities.…”
mentioning
confidence: 99%
“…The HKTP has found that asking patients to bring "living donors" can reduce their willingness to participate and result in patients not asking their family to donate, which has been observed elsewhere. 17,19,30 Further, Hispanic family members often do not realize their potential eligibility to donate, given a lack of knowledge and cultural concerns about LKD and transplantation. Thus, the HKTP, by inviting family members in the education sessions, aims to enhance knowledge about transplantation and donation throughout the family, which increases family members' consideration of becoming a living donor, and plays an important role in moving along treatment decisions because Hispanic family elders (e.g., the grandmother) often influence and guide these decisions.…”
Section: Hktp's Core Featuresmentioning
confidence: 97%
“…12 In our earlier clinical experience (JCC), Hispanic patients were reluctant to identify and bring potential living donors with them to the transplant education session. Concerns about LDKT that Hispanics share with other minority groups include: lack of knowledge about LKD, 13,[16][17][18] fear of surgery, 12,17,18 financial concerns, 13,17,19 and distrust of the medical establishment. 15,17,18 Provider factors include lack of Hispanic health care providers, low rates of preemptive transplantation, and of referral for transplantation.…”
mentioning
confidence: 99%
“…However, reasons for these reported difficulties identifying potential donors are poorly understood. Some prior studies suggest that racial–ethnic minority patients may be more likely to encounter difficulties in identifying potential donors who meet medical criteria for donation . Other studies question whether difficulties may be due to racial–ethnic minorities’ poor willingness to donate .…”
mentioning
confidence: 99%